SELF-MANAGEMENT IN PATIENTS WITH ASTHMA BRONCHIAL - Cut Husna (Fakultas Keperawatan-Universitas Syiah Kuala, 2010)
ABSTRACTThe burden of asthma affects the patients, families, society in terms of lost work, lessened quality of life,hospitalizations, and death. Continuing adult asthma morbidity is evident in the increasing number ofoutpatient and emergency visits to asthma. Many factors described as possible causes for the increasedmorbidity and mortality includes poor patient understanding of the disease process in appropriatemedication use, non adherence with prescribe preventive medication, and poor inhaler technique. Becauseof the asthma impact of rising severity, morbidity and mortality for human being, self-management is animportant things developed for asthma patients to improve self-care and maintain healthy life. Many ofpeople are associated with self-management, particularly patients, caregivers, health care providers, andpolicy providers to make a planning partnership in caring asthma patients. The self-management that involvefour components namely assessing and monitoring asthma severity and asthma control, education forpartnerships in care, control of environment factors and comorbid condition, and medications. The design ofstudy was descriptive explorative for three patients in Songkla Nagarind Hospital, Hatyai, Thailand. The aimof study was to describe the phenomenon of self-management in patients with asthma by using fourquestionnaires that consisted of ASQ, ACQ, ACECC, and MARS. Data collection divided into two parts waspretest and posttest, except for asthma severity only for pretest because its focused to identify level of asthmaseverity. The study was analyzed by using descriptive statistic with mean (X) and standard deviation (SD).The result of the study showed that asthma severity for mild, moderate, and severe levels for patients 1, 2 and3. Moreover, asthma control was moderate level, control of environment factor and comorbid conditions wasmoderate level, and medication adherence was moderate level as well. These components could be improvein asthma care and significantly reduce asthma trigger and statistically can be viewed as effective cost waysto maintain quality of life in asthma patients.Keyword: self-management, asthma bronchial, patients’ admitted, hospital